First case of laparoscopic partial splenectomy in a child with hamartoma: Case report and review of the literature. (2018) - Serra, Francesco; Sorrentino, Lorena; Cabry, Francesca; Biondini, Diego; Ceccarelli, Pier Luca; Campanelli, Michela; Gelmini, Roberta
Highlights: Laparoscopic surgery as technique of choice in children for benign solid lesions of the spleen. Multidisciplinary treatment of rare disease, Hamartoma of the spleen, in childhood. Role of chemoembolization in the pre-operative surgical setting to reduce intraoperative bleeding. Partial splenectomy as safe procedure to preserve hematological function of the spleen. Abstract: Introduction: To date, laparoscopic surgery has played a key role in the treatment of not only splenic hematologic pathologies but also solid ones. Hamartoma is a rare disease; only twenty percent of them are of pediatric relevance; it is a benign tumor, but radiological features never allow proper differentiation from malignant neoplasms. In children, hamartoma may be associated with other morbid conditions, such as sickle cell disease or other hematological alterations. Presentation of the case: We report a case of hamartoma in a 7-year-old child treated with partial laparoscopic splenectomy. After a multidisciplinary evaluation, the indication of laparoscopic splenectomy was decided; upon evaluating the age of the patient and the affected spleen portion, a partial splenectomy was proposed. The histological examination during surgery was performed to exclude any form of malignancy. The intraoperative frozen section of the specimen was negative for malignancies, and a partial splenectomy was performed. Discussion: Surgery remains the first choice in the definitive treatment of solid lesions of the spleen; minimally invasive technique, namely, laparoscopy, has set itself as the technique of choice for surgical treatment. In this case, the possibility of obtaining an intraoperative pathological diagnosis by frozen section of the specimen, confirming the benign nature of the lesion, allowed the surgeon to decide in favor of a laparoscopic partial splenectomy. Conclusion: Partial laparoscopic splenectomy can be considered a safe, effective and reproducible alternative in patients suffering from benign solid diseases, safeguarding the hematological functions of the organ itself in pediatric age.